Analisis Permasalahan Kantor Cabang Koperasi CU. Harapan Kita - Perkasa, Ripho Delzy; Alwi, Ahmad; Hasibuan, Sarah Nadia; Alfarisi, Salman (As-Syirkah: Islamic Economic & Financial Journal, 2024)
This research analyzes and examines problems within cooperative organizations, especially internal and external problems that occur. According to cooperative law, cooperatives are business entities consisting of people or cooperative legal entities that base their activities on cooperative principles, as well as being a people's economic movement based on Based on deficiencies in posting posts, an organization will definitely have problems. Therefore, the research aims to uncover the problems that exist in CU cooperatives. Our expectation. The data collection technique used in this research is through observation, interviews and documentation, as well as using qualitative descriptive research methods. This research will show the causes of the problem and how the cooperative handles the problem. The research results show a lack of development of effective marketing strategies, dependence on limited capital sources, lack of member involvement in strategic decision making, as well as problems related to employee loans and bad credit for customers.